PENGARUH KINERJA BANK, SOLVABILITAS, LIKUIDITAS DAN NON PERFORMING FINANCING TERHADAP RISIKO LIKUIDITAS PADA BANK UMUM SYARIAH DI INDONESIA - Cut Dini Monisa; Wida Fadhlia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this study is to examine the effect of bank performance, solvability, liquidity, and non performing financing to ward the liquidity risk in sharia bank in Indonesia from 2011 to 2015. In this research, there were 11 sharia banks in total that were taken as sample. These banks published annual report during 2011 to 2015. The type of data used was secondary data. In order to get the result of this research, the author has examined the form of financial statements of sharia banks which had 55 financial statements in five years. Furthermore, the hypothesis testing used was multiple linear regression test.Bank performance was measured by using CAR, meanwhile solvability was measured by using DER, and the last one, liquidity, was measured by using FDR. The results of this study showed that capital adequacy ratio, debt to equity ratio, financing to deposit ratio, and non performing financing affected the liquidity risk simultaneously. Capital adequacy ratio, financing to deposit ratio, and non performing financing partially have a positive and significant impact on liquidity risk, while debt to equity ratio has a negative and significant effect on liquidity risk.